(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the historical role and activities of Saroymulk Khanum (Bibi Khanum), a prominent figure of the Timurid Empire. The study analyzes her influence on Amir Temur’s political policies, her leadership in scholarly and cultural spheres, her decision-making in critical situations, and her contributions to urban development based on historical sources. In addition, the position of women in the state and society during the Timurid period is explored through the example of Saroymulk Khanum, and her historical legacy is evaluated from a scholarly perspective.